Mobile Phones, Non-Ionizing Radiofrequency Fields and Brain Cancer: Is There an Adaptive Response? - Vijayalaxmi; Thomas J. Prihoda (SAGE Publishing, 2014)
There is widespread concern among the general public regarding the ever increasing use of mobile phones. The concern is mainly because the antenna which transmits non-ionizing radiofrequency fields is held close to the head during use and thus might cause brain cancer. By far, the largest epidemiological study was conducted by the INTERPHONE study group and the results were published in 2011. The author's conclusions were (i) no increased risk of meningioma and glioma in mobile phone users and (ii) there were suggestions of an increased risk for glioma at the highest exposure levels but, bias and error prevented a causal interpretation. We have carefully examined all of the odd ratios presented in the INTERPHONE study publication: our results showed 24.3% decreased and 0.7% increased risk for meningioma and 22.1% decreased and 6.6% increased risk for glioma. Hence, we hypothesize that the overwhelming evidence for the decreased risk for both diseases may be due to the induction of 'adaptive response' which is well-documented in scientific literature